2015
DOI: 10.1542/peds.2014-4075
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Morbidity and Mortality of Extremely Preterm Multiple Gestation Newborns

Abstract: To examine the risk of mortality and major morbidities in extremely preterm multiple gestation infants compared with singletons over time.METHODS: This is a retrospective study of 15 402 infants born #27 weeks' gestation, admitted to NICUs in the Australian and New Zealand Neonatal Network from 1995 to 2009. Mortality and major morbidities were compared between singletons and multiples across three 5-year epochs.RESULTS: Extreme preterm multiples were more likely to have lower birth weight; higher maternal age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 33 publications
5
25
0
Order By: Relevance
“…These pregnancies are closely monitored and managed in specialized multiple pregnancy clinics in our institution and appropriate intervention is offered when deemed necessary such as use of antenatal steroids in the presence of threatened preterm labor. Similar to our findings, Yeo et al 11 and Nielson et al 24 have shown a significantly higher rate of cesarean delivery and use of antenatal steroids in preterm VLBW multiples. Vulić has shown a higher incidence of cesarean delivery in multiple births conceived by ART.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These pregnancies are closely monitored and managed in specialized multiple pregnancy clinics in our institution and appropriate intervention is offered when deemed necessary such as use of antenatal steroids in the presence of threatened preterm labor. Similar to our findings, Yeo et al 11 and Nielson et al 24 have shown a significantly higher rate of cesarean delivery and use of antenatal steroids in preterm VLBW multiples. Vulić has shown a higher incidence of cesarean delivery in multiple births conceived by ART.…”
Section: Discussionsupporting
confidence: 92%
“…This gender disadvantage has been demonstrated in a local study by Agarwal et al in infants born extremely preterm between 23 and 26 weeks 30 as well as other international studies. 11,31 Recent Spanish network data 29 documented a higher risk of composite adverse outcome with OR of 1.82 (95% CI: 1.28-2.24) in multiples born less than 26 weeks of gestational age similar to ours. However, Yeo et al did not show any difference in the major neonatal morbidities or composite adverse outcome between singletons and multiples at this gestation and postulated this improvement could be due to closer monitoring and improved perinatal care of these highrisk pregnancies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The impact of birth weight and the other a priori selected variables on death and death and major morbidity combined was remarkably similar. Multiple gestation was not linked to poor outcome, an observation made for recent cohorts also in Australia and New Zealand ( 23 ). Small for gestational age was associated with reduced ORs for poor outcome as the investigation used birth weight as primary variable, the opposite would have been observed with gestational age as primary variable.…”
Section: Discussionmentioning
confidence: 85%
“…In singleton, survival to discharge following delivery at 24, 25, and 26 weeks is 31.2%, 59.1%, and 75.3%, respectively [ 5 ]. In multiples, the mortality rate was 32% from 23 to 25 weeks' gestational age, compared to 19.2% from 26 to 27 weeks' gestational age and 11.1% in all gestational age [ 6 ]. At these extremely premature gestational ages, even small increases in gestational age have tremendous impact on neonatal survival [ 5 ].…”
Section: Introductionmentioning
confidence: 99%